Utilization of the national cluster of district health information system for health service decision-making at the district, sub-district and community levels in selected districts of the Brong Ahafo region in Ghana - Eliezer Ofori Odei-Lartey; Rebecca Kyerewaa Dwommoh Prah; Edward Apraku Anane; Harry Danwonno; Stephaney Gyaase; Felix Boakye Oppong; Godwin Afenyadu; Kwaku Poku Asante (BMC, 2020)
Abstract Background There is growing interest in the use of reliable evidence for health decision-making among low-and middle-income countries. Ghana has deployed DHIMS2 to replace the previously existing manual data harmonization processes. Methods This cross-sectional study was conducted in 12 districts comprising 12 district directorates, 10 district hospitals, 29 sub-district health centers, and 38 community health facilities in the Brong-Ahafo Region. Data collection tools were developed based on the Measure Evaluate assessment tools designed for evaluating the performance of routine information systems management tools. Utilization was assessed based on documented evidence and data was analyzed using STATA version 14. Results Although 93% of the health facilities studied submitted data unto the DHIMS2 platform, evidence suggested low use of this data in decision-making, particularly at the community level facilities where only 26% of the facilities used data from DHIMS2 to inform annual action plans and even less than 20% examined findings and issued directives for action. At the district level, 58% issued directives based on DHIMS2 information, 50% used DHIMS2 information for Advocacy purposes and 58% gave feedback reports based on DHIMS2 data for action. Functional computers were lacking across all facilities. Conclusions Activities relating to the use of DHIMS2 information skew towards data quality checking with less focus on examining findings, making comparisons, and taking action-based decisions from findings and comparisons. Improving factors like internet access, availability of functional ICTs, frequency of supervisory visits, staff training and the provision of training manuals may facilitate the use of DHIMS2 in decision-making at all levels of the district health system.